The Effect of Product Diversity and Service Quality on Marketing Performance through Competitive Advantages - Andi Muhammad Dhaifullah; Musran Munizu; Fauziah Umar (Hasanuddin Journal of Business Strategy, 2021)
This study aims to analyze the effect of product diversity and service quality on competitive advantage as well as the effect of product diversity, service quality, and competitive advantage on marketing performance in the case of two retailer companies, Hero and Transmark. Data collected 100 consumers with the distribution of questionnaires. The data is then analyzed using path analysis. The results of the study found that product diversity and service quality had a positive and significant effect in increasing competitive advantage. Product diversity, service quality, and competitive advantage can have a meaningful effect in improving marketing performance. Competitive advantage can partially mediate the effect of product diversity on marketing performance and also the effect of service quality on marketing performance at Hero and Transmart supermarkets.